Gruppenaufnahme
Ministerpräsident Italien Giulio Andreotti; Premieminister Großbritannien James Callaghan; Staatspräsident Frankreich Valéry Giscard d'Estaing; Bundeskanzler Helmut Schmidt; Ministerpräsident Luxemburg Gaston Thorn; Ministerpräsident Belgien LeoTindemans; Ministerpräsident Dänemark Anker Joergensen;